2020
DOI: 10.1073/pnas.2001529117
|View full text |Cite
|
Sign up to set email alerts
|

Template-stabilized oxidic nickel oxygen evolution catalysts

Abstract: Earth-abundant oxygen evolution catalysts (OECs) with extended stability in acid can be constructed by embedding active sites within an acid-stable metal-oxide framework. Here, we report stable NiPbOx films that are able to perform oxygen evolution reaction (OER) catalysis for extended periods of operation (>20 h) in acidic solutions of pH 2.5; conversely, native NiOx catalyst films dissolve immediately. In situ X-ray absorption spectroscopy and ex situ X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 61 publications
5
47
0
Order By: Relevance
“…For this purpose, numerous research groups have been working on the development of transition metal oxides for OER in acid. [ 192–204 ] Mn‐based oxides and Co‐based oxides are the two most widely investigated transition metal oxides. First, Mn‐based oxides are considered for OER in acid due to the nature of self‐healing to compensate their dissolution in acid.…”
Section: Electrocatalysts For Oer In Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, numerous research groups have been working on the development of transition metal oxides for OER in acid. [ 192–204 ] Mn‐based oxides and Co‐based oxides are the two most widely investigated transition metal oxides. First, Mn‐based oxides are considered for OER in acid due to the nature of self‐healing to compensate their dissolution in acid.…”
Section: Electrocatalysts For Oer In Acidmentioning
confidence: 99%
“…First, Mn‐based oxides are considered for OER in acid due to the nature of self‐healing to compensate their dissolution in acid. [ 192 ] Up to now, numerous Mn‐based oxides have been fabricated and optimized, such as TiO 2 ‐incorporated MnO 2 , [ 138 ] hausmannite‐like intermediate (α‐Mn 3 O 4 ), [ 193 ] MnO 2 with metastable Mn 3+ , [ 194 ] Co/Mo‐doped MnO 2 (MnMoCoO), [ 195 ] Cu 1.5 Mn 1.5 O 4 :10F, [ 196 ] Ni x Mn 1− x Sb 1.6–1.8 O y , [ 197 ] (Mn 0.9 Nb 0.1 )O 2 :10F, [ 198 ] NiPbO x , [ 199 ] etc. Among these Mn‐based oxides, the well‐designed gamma manganese oxides (γ‐MnO 2 ) showed a long‐term stability of 8000 h between 1.6 and 1.75 V versus RHE (at 10 mA cm −2 ) in a pH = 2 electrolyte.…”
Section: Electrocatalysts For Oer In Acidmentioning
confidence: 99%
“…Iron doping of metal oxide films has long been known to increase overall OER activity of metal oxide OER catalysts 42,43 . The behaviour of Fe in Ni-OECs has been revisited 44 , and the role of Fe has been ascribed to various factors, including active site Fe 4 + or higher valent species [45][46][47] , near neighbour Fe effects on Ni resulting from strain on the oxide lattice [48][49][50][51] , active oxygen intermediates at Ni-Fe sites [52][53][54] , Fe induced partial-chargetransfer to Ni sites 55,56 , and Fe acting as a Lewis acid that promotes charge transfer character and favourable energetics for Ni oxyl formation 57,58 . Quizzically, though detected by Mössbauer spectroscopy, the presence of Fe 4+ does not correlate with the observed catalytic activity 59 .…”
mentioning
confidence: 99%
“…tested the in situ XAS of stable NiPbO x films (Figure 11D), combined ex situ X‐ray photoelectron spectroscopy (Figure 11C) found that PbO 2 is unperturbed after addition of Ni and/or Fe into the lattice, which serves as an acid‐stable, conductive framework for embedded OER active centers. [ 159 ]…”
Section: In Situ Characterizations For Acidic Oermentioning
confidence: 99%
“…Reproduced with permission: Copyright 2020, PNAS. [ 159 ] (E,F) In situ XANES spectra of Li‐IrO x and IrO 2 ‐L. (G,H) In situ EXAFS spectra of Li‐IrO x and IrO 2 ‐L.…”
Section: In Situ Characterizations For Acidic Oermentioning
confidence: 99%